Phytochemical screening and in vitro antimicrobial activity of Bougainvillea spectabilis flower extracts - Kumara Swamy M; Sudipta KM; Lokesh P; M Neeki A; Rashmi W; S Bhaumik H; S Darshil H; R Vijay; SSN Kashyap (International Journal of Phytomedicine, 2012)
Various flower extracts (Chloroform, ethyl acetate, ethanol and water) of Bougainvillea spectabilis were screened for their phytochemical constituents and also investigated for their antimicrobial activities. Phytochemical screening of flower extracts revealed the presence of alkaloids, flavonoides, phlobatannins and terpenoids. Steroids, phenol, tannins, cardinolides and volatile oils were absent in all the extracts. All flower extracts of B. spectabilis inhibited the growth of few of the bacterial and fungal strains tested with varied effectiveness. The maximum antibacterial activities were observed in ethanol and water extracts. The maximum antifungal activities were observed in chloroform and ethanol extracts. Thus the bioactive natural products in flower extracts of Bougainvillea spectabilis can be used in the development of new pharmaceuticals that address unmet therapeutic use.